A Religious Psychology-Based Reconstruction Model for Strengthening Students’ Spiritual and Moral Attitudes in Islamic Religious Education - Rizqia Ulfa; Salami Mahmud; Wanty Khaira (IQRO: Journal of Islamic Education, 2026)
Islamic Religious Education faces challenges in helping students internalize spiritual and moral values because it remains focused on cognitive aspects. This situation is further exacerbated by the rise of digitalization and the use of conventional teaching methods that are less effective at fostering students’ emotional engagement. This study aims to analyze the current state of spiritual and moral attitude formation, identify the limitations of the learning approaches used, and formulate a model for reconstructing spiritual and moral attitude formation based on the psychology of religion. The study employs a library research method with a qualitative approach. Data were collected through documentary studies and a review of scientific literature using Google Scholar and the Publish or Perish (POP) application. Data sources include academic literature from the past ten years and PAI curriculum documents. Data analysis was conducted using content analysis techniques. The research hypothesis states that the implementation of PAI learning based on the psychology of religion influences the improvement of students’ spiritual and moral attitudes. The results of the study indicate that a learning model integrating contextual understanding, habitual practice, reinforcement of religious emotions, and the unification of values is capable of enhancing moral internalization. Additionally, the utilization of digital media and the transformation of tauhid values in the educational leadership contribute to building a holistic learning ecosystem focused on character development.